2018
DOI: 10.1016/j.nicl.2018.06.019
|View full text |Cite
|
Sign up to set email alerts
|

It takes two to pantomime: Communication meets motor cognition

Abstract: For over a century, pantomime of tool use has been employed to diagnose limb apraxia, a disorder of motor cognition primarily induced by left brain damage. While research consistently implicates damage to a left fronto-temporo-parietal network in limb apraxia, findings are inconsistent regarding the impact of damage to anterior versus posterior nodes within this network on pantomime. Complicating matters is the fact that tool use pantomime can be affected and evaluated at multiple levels. For instance, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 64 publications
3
62
0
1
Order By: Relevance
“…A plethora of VLBM studies utilised nuisance regression or similar approaches to control the variable of interest for the variance explained by additional behavioural variables (e.g., Almairac et al, ; Baldo et al, , ; Finkel et al, ; Gajardo‐Vidal et al, ; Jones et al, ; Lorca‐Puls et al, ; Martin et al, ; Moon et al, ; Pillay et al, , ; Schwartz et al, ; Walker et al, ; Wilson et al, ; Winder et al, ). While some previous studies provide a rationale for covariate control, others do not provide any rationale at all or simply resort to a data driven procedure, where all known variables that correlate with the target symptom are controlled for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plethora of VLBM studies utilised nuisance regression or similar approaches to control the variable of interest for the variance explained by additional behavioural variables (e.g., Almairac et al, ; Baldo et al, , ; Finkel et al, ; Gajardo‐Vidal et al, ; Jones et al, ; Lorca‐Puls et al, ; Martin et al, ; Moon et al, ; Pillay et al, , ; Schwartz et al, ; Walker et al, ; Wilson et al, ; Winder et al, ). While some previous studies provide a rationale for covariate control, others do not provide any rationale at all or simply resort to a data driven procedure, where all known variables that correlate with the target symptom are controlled for.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of VLBM studies utilised nuisance regression or similar approaches to control the variable of interest for the variance explained by additional behavioural variables (e.g., Almairac et al, 2015;Baldo et al, 2013Baldo et al, , 2018Finkel et al, 2018;Gajardo-Vidal et al, 2018;Jones et al, 2016;Lorca-Puls et al, 2018;Martin et al, 2017;Moon et al, 2018;Pillay et al, 2014Pillay et al, , 2017Schwartz et al, 2011;Walker et al, 2011;Wilson et al, 2015;Winder et al, 2016).…”
mentioning
confidence: 99%
“…First, the above reported findings from mass-univariate studies already identified different areas that are spread across the brain, and that might be cortical nodes of such network. This point is also supported by componential analyses, that investigated multiple different sub-symptoms of pantomime (Manuel et al, 2013;Finkel et al, 2018). These studies found different areas to underlie behavioural components of apraxia, which could be part of a network for motor control.…”
Section: Introductionmentioning
confidence: 61%
“…Goldenberg et al, 2007;Manuel et al, 2013;Hoeren et al, 2014), but also in single cases (Kertesz and Ferro, 1984) and by a fMRI-DTI study (Vry et al, 2015). Thus, damage to a brain network of multiple cortical regions that are connected by white matter fibres likely underlies apraxia (see also Niessen et al, 2014;Vry et al, 2015;Finkel et al, 2018;Buxbaum & Randerath, 2018), which already has been postulated in classical models of praxis skills by Liepmann and Geschwind (see Buxbaum & Randerath, 2018).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation